КОНСТРУИРОВАНИЕ И ВЫБОР ВЕЙВЛЕТОВ ДЛЯ АНАЛИЗА ТЕПЛОВЫХ ПРОЦЕССОВ В СИЛОВОМ ТРАНСФОРМАТОРЕ - Поляков , М.А. (Інститут електродинаміки НАН України, Київ, 2012)
According to the numerical representation of the basic wavelets for discrete wavelet-transformation, the form of test load currents of the power transformer (PT) are defined. For these currents, the computer modeling of thermal processes in PT is executed. The hot spot temperature and the loss of the winding isolation life of caused by thermal deterioration are defined. Wavelets, which correspond to test current, which influence on PT leads to max/min values of these parameters, are chosen as basis wavelets for reception of wavelet spectrum of PT monitoring data. Value and dynamic spectrum factors characterise critical thermal processes in the PT. Reference 1, table 1.